Equity Prices, Credit Default Swaps, and Bond Spreads in Emerging Markets - Chan-Lau, Jorge (IMF Working Papers; Working Paper, 2004)
This paper examines equilibrium price relationships and price discovery between credit defaul swap (CDS), bond, and equity markets for emerging market sovereign issuers. Findings suggest that CDS and bond spreads converge despite various pressures that arise in the market. In most countries, however, we do not find any equilibrium price relationship between the bond and CDS markets and the equity markets. As for price discovery, our results are mixed. This stands in contrast to the empirical findings on corporate issuers in the United States and Europe.